Quality of survival: a new concept framework to assess the quality of prolonged life in cancer. Issue 4 (4th July 2017) - Fallowfield, Lesley; Nadler, E.; Gilloteau, I.; Greaney, M.; Gater, A.; Orsini, L.; Subar, M.; Lyman, G. H.
ABSTRACT: Background: Improved cancer care means that more patients are surviving longer, but there is a need to examine how well patients survive. We conducted an exploratory analysis of a new conceptual framework termed 'quality of survival' (QoS) that delineates the quality of patients' experience. Methods: This project included an electronic database search to investigate the survivorship landscape and to create a visual QoS map and semi-structured interviews with patients (n = 35), clinicians (n = 40), and payers (n = 7) to support the QoS map. QoS was discussed in the context of two tumor types, metastatic non-small cell lung cancer and metastatic melanoma. Results: Despite increased long-term survival, no specific definition of QoS exists. Patients reported many impacts that affect QoS, clinicians viewed QoS as relevant to treatment decisions, and payers felt it could help communicate different aspects relevant to the patient. Four interconnected QoS dimensions were developed (quality of life, survival, side effects, and economic impact), which vary in importance along the care continuum. Conclusion: QoS is a patient-centric concept that could help decision-making and patient communication. The QoS map could provide a framework to monitor patient experience and help patients frame what treatment attribute is most important to them at any point in the cancer continuum.